Fabrication of Naturally Derived Double-Network Hydrogels With a Sustained Aspirin Release System for Facilitating Bone Regeneration - Zhu, Wenfeng; Chen, Rui; Wang, Weiheng; Liu, Yi; Shi, Changgui; Tang, Songjun; Tang, Guoke (Frontiers in Chemistry, 2022)
Continuous efforts on pursuit of effective drug delivery systems for engineering hydrogel scaffolds is considered as a promising strategy for the bone-related diseases. Here we developed a kind of acetylsalicylic acid (aspirin, ASA)-based double-network (DN) hydrogel containing the positively charged natural chitosan (CS) and methacrylated gelatin (GelMA) polymers. Combination of physical chain-entanglement and electrostatic interactions and chemically crosslinked methacrylated gelatin (GelMA) network led to the formation of DN hydrogels, which had suitable porous structures and favorable mechanical properties. After in-situ encapsulation of the aspirin agents, the resulting hydrogels were investigated as culturing matrices for adipose tissue-derived stromal cells (ADSCs) to evaluate their excellent biocompatibility and biological capacities on modulation of cell proliferation and differentiation. We further found that the long term of sustained ASA in the DN hydrogels could contribute to the anti-inflammation and osteoinductive properties, demonstrating a new strategy for bone tissue regeneration.